Antibacterial Potential of Ethanolic Extract of Avocado Leaves (Persea americana mill.) against Clinical Isolate of Klebsiella pneumoniae and Proteus mirabilis - Nasri, Nasri; Satria, Denny; Kaban, Vera Estefania; Tania, Chyntia Glori; Syahputra, Hariyadi Dharmawan; Rani, Zulmai (Trends in Sciences, 2024)
Multidrug resistance is a global health problem that is closely related to microbial resistance. Klebsiella pneumonia and Proteus mirabilis are opportunistic bacteria that cause urinary tract infections, especially in the use of catheters in hospitals in inpatient care. Handling it using commercial antibiotics can increase the effect of antibacterial resistance if the use is irrational and neglected. Avocado leaves have been reported to have antibacterial, antidiabetic and antioxidant activity. The purpose of this study was to observe into the antibacterial activity of avocado leaves ethanol extract against K. pneumoniae and P. mirabilis. The minimum inhibitory concentration (MIC) was determined using the Kirby-Bauer method, the minimum bactericidal concentration (MBC) was determined using the streaking method of the inhibition zone formed, and the mechanism of bacterial membrane leakage cell was measured using UV-VIS spectrophotometry at wavelengths of 260 and 280 nm. The MIC value was found to be 3.125 mg/mL in both bacteria, with an inhibition zone of 6.43 ± 0.06 mm (K. pneumoniae) and 6.73 ± 0.15 mm (P. mirabilis). The MBC value at 200 mg/mL with a percent reduction of 98.35 % (K. pneumoniae) and at 100 mg/mL with a percent reduction of 98.06 % (P. mirabilis). The supernatant of a membrane leakage cell (DNA and protein) was absorbed at wavelengths of 260 and 280 nm. It can be concluded that the ethanolic extract of avocado leaves has antibacterial potential against clinical isolates of K. pneumoniae and P. mirabilis. HIGHLIGHTS Avocado leaves, which are typically discarded, can be repurposed as a potent antibacterial agent in traditional medicine Demonstrates a potent minimum inhibitory concentration with a minimum bactericidal concentration value that can effectively suppress bacterial growth Point number 2 is substantiated by the utilization of DNA and protein cell leakage tests, as evidenced by absorbance measurements at wavelengths of 260 and 280 nm Flavonoid secondary metabolite have been successfully identified as one of the active components using the TLC analysis method GRAPHICAL ABSTRACT